PENINGKATAN AKTIVITAS SISWA KELAS V SD PADA PEMBELAJARAN ANSAMBEL MUSIK MELALUI STRATEGI PAIKEM - Asma Ulhusna; Syeilendra Syeilendra; Ardipal Ardipal (FBS Universitas Negeri Padang, 2013)
Abstract This research was done due to the lack of student’s in learning arts at SD Negeri 18 Koto Tangah Tilatang Kamang. The lack of activities was caused by the unvaried learning method being used at the school. To overcome the problem, the PAIKEM strategy was applied in this class action research. This research aimed at improving the fifth grade student’s activities in learning arts. Based on the data analysis, it was found that the use of PAIKEM in arts improved student’s activities. It was seen from the percentage of 78.5% for student’s attention to teacher, 62.0% for student’s exercises, 27.3% for student’s questions towards their learning, and 54.0% for their participations in front of the class. Kata kunci: Activities,Ansamble,PAIKEM